Antcin-H, a natural triterpene derived from Antrodia cinnamomea, ameliorates dextran sulfate sodium-induced colitis in mice by inhibiting the NLRP3 inflammasome - Wei-Ting Wong; Lan-Hui Li; Hsiao-Wen Chiu; Mridula P. Menon; Hsien-Ta Hsu; Wen-Yu Lin; Chun-Hsien Wu; Chen-Lung Ho; Kuo-Feng Hua (Journal of Traditional and Complementary Medicine)
Inflammatory bowel disease (IBD) comprises idiopathic intestinal disorders, including ulcerative colitis and Crohn's disease. Patients with IBD experience a significantly reduced quality of life, and effective management remains challenging. The NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome controls the expression of the pro-inflammatory cytokines interleukin (IL)-1β and IL-18. Abnormal activation of the NLRP3 inflammasome is a crucial factor in the pathogenesis of IBD, making it an attractive therapeutic target. We discovered that Antcin-H, a triterpene isolated from the unique medicinal fungus Antrodia cinnamomea found in Taiwan, effectively inhibits the NLRP3 inflammasome in macrophages and alleviates dextran sulfate sodium (DSS)-induced colitis in a mouse model. We noted that Antcin-H effectively suppresses the NLRP3 inflammasome in macrophages by diminishing reactive oxygen species production, alleviating mitochondrial damage, and reducing apoptosis-associated speck-like protein containing a CARD (ASC) oligomerization. Importantly, these effects are achieved without impacting NF-κB activation. Oral administration of Antcin-H improved symptoms such as diarrhea, bloody stool, weight loss, colon length shortening, and splenomegaly in DSS-treated mice. Antcin-H inhibits colonic expression of NLRP3, ASC, active caspase-1, IL-1β, IL-6, tumor necrosis factor-alpha, monocyte chemoattractant protein-1, myeloperoxidase, C-X-C motif chemokine ligand 1, and cyclooxygenase-2 in DSS-treated mice. Furthermore, Antcin-H modulates the colonic expression of long non-coding RNAs involved in the regulation of NLRP3 inflammasome activation. These results indicate that Antcin-H has the potential to improve IBD by reducing colonic inflammation and suppressing NLRP3 inflammasome activation.